SIKAP MODERASI BERAGAMA SISWA MADRASAH ALIYAH: STUDI TERHADAP PEMANFAATAN CANDI SEBAGAI TEMPAT IBADAH - Iwan Setiadi; Nurmala Nurmala; Septiana Zahara Rizka (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2022)
Abstract Indonesian Ministry of Religion Instagram content contains information on signing an agreement regarding using Prambanan and Borobudur Temples as places of religious activities for Hindus and Buddhists. This content elicited various reactions from netizens. The aims of the study were to 1) find out the relationship between attitudes of religious moderation and attitudes regarding the MoU on the use of Prambanan and Borobudur temples as places of Hindu-Buddhist religious activities in Indonesia and the World; 2) Describe the relationship between attitudes of religious moderation and attitudes regarding the MoU on using Prambanan and Borobudur Temples as places of Hindu-Buddhist religious activities in Indonesia and the World. The research method used is mixed methods with an explanatory sequential design. Data collection techniques used questionnaires, interviews, and documentation studies from the Instagram content of the Ministry of Religion of the Republic of Indonesia. Respondents were randomly obtained from 250 students of Madrasah Aliyah North Jakarta City. The analysis technique uses the correlation test, calculates the average gain of the scale, and reduces irrelevant data. The results of the study show that: 1) There is a positive relationship between attitudes of religious moderation and attitudes regarding the MoU on the use of Prambanan and Borobudur Temples as places of Hindu-Buddhist religious activities in Indonesia and the World; 2) The attitude of religious moderation of madrasah aliyah students is classified as very high, with an average acquisition of a scale of 4.32. In addition, students' attitude towards the use of the temple corresponds to the student's attitude regarding moderation in religion.   Abstrak Konten instagram Kementerian Agama RI berisi informasi penandatanganan kesepakatan mengenai pemanfaatan Candi Prambanan dan Borobudur sebagai tempat kegiatan keagamaan umat Hindu dan Buddha. Konten ini menimbulkan beragam reaksi dari warganet. Tujuan penelitian adalah untuk: 1) Mengetahui hubungan antara sikap moderasi beragama dengan sikap mengenai MoU pemanfaatan Candi Prambanan dan Borobudur sebagai tempat kegiatan keagamaan Hindu-Buddha di Indonesia dan Dunia; 2) Mendeskripsikan hubungan antara sikap moderasi beragama dengan sikap mengenai MoU pemanfaatan Candi Prambanan dan Borobudur sebagai tempat kegiatan keagamaan Hindu-Buddha di Indonesia dan Dunia. Metode penelitian yang digunakan adalah mixed methods dengan rancangan sekuensial eksplanatori. Teknik pengambilan data menggunakan angket, wawancara, dan studi dokumentasi dari konten instagram Kementerian Agama RI. Responden diperoleh secara acak sejumlah 250 orang siswa Madrasah Aliyah Kota Jakarta Utara. Teknik analisis mengunakan uji korelasi, menghitung rerata perolehan skala dan mereduksi data yang tidak relevan. Hasil penelitian menunjukkan bahwa: 1) Terdapat hubungan yang positif antara sikap moderasi beragama dengan sikap mengenai MoU pemanfaatan Candi Prambanan dan Borobudur sebagai tempat kegiatan keagamaan Hindu-Buddha di Indonesia dan Dunia; 2) Sikap moderasi beragama siswa madrasah aliyah tergolong sangat tinggi dengan perolehan rerata skala 4,32. Selain itu sikap siswa terhadap pemanfaatan candi bersesuaian dengan sikap moderasi beragama siswa.